The Motive for Using @schfess Twitter Account to Meet the Followers’ Information Needs - Selviana, Selviana; Wanastri, Prisinta (Syarif Hidayatullah State Islamic University of Jakarta, 2023)
Currently, social media is widely used as a source of information by its users to meet their information needs. This study aims to determine the motives of followers to use the Twitter account @schfess as a means of fulfilling their information needs. This study uses quantitative descriptive research methods with survey data collection techniques, namely distributing questionnaires to 100 respondents who are followers of the @schfess Twitter account. The data analysis technique used is descriptive analysis of the percentage. The results show that there are four types of motives that encourage someone to use social media with the information motive having the highest average value of 3.52 which is included in the